Design and Development of Monolithic Microwave Integrated Amplifiers and Coupling Circuits for Telecommunication Systems Applications - R. Makri; M. Gargalakos; N. K. Uzunoglu (Active and Passive Electronic Components)
Recent advances in printed circuit and packaging technology of microwave and millimeter wave circuits result to the increasing use of MMICs in telecommunication systems. At Microwave and Fiber Optics Lab of NTUA several designs of various MMICs were conducted using the HP Eesof CAD Tool and FET and HEMT models of F20 and H40 GaAs foundry process of GEC Marconi. The designed MMICs are constructed in Europractice Organization while on-wafer probe measurements are performed in the Lab. In that framework, MMIC technologies are employed in the design of power and low noise amplifiers and couplers to be used for mobile and wireless communications as well as remote sensing and radar applications. A medium power linear FET amplifier has been designed with combining techniques on a single chip. The circuit operates at 14.4–15.2 GHz with an input power of −15 dB m, a 36 dB total gain, while the input and output VSWR is less than 1.6. Due to high cost of MMIC fabrication only the first subunit was manufactured and tests verified the simulation results. Additionally, novel techniques have been used for the design of two coupling networks at 10 GHz in order to minimize the area occupied. A meander-kind design as well as shunt capacitors were implemented for a 90° quadrature coupler and a Wilkinson one in order to reduce size. Finally, a two stages low noise amplifier was designed with the use of H40 GaAs process in order the differences between the relevant designs to be explored. The key specifications for this MMIC LNA include operation at 10 GHz with a total gain of 17 dB while the noise figure is less than 1.5 dB.